Fabrication of a uniaxial cellulose nanocrystal thin film for coassembly of single-walled carbon nanotubes. Issue 45 (19th April 2016) - Yang, Danqin; Lu, Zihao; Qi, Xiaoqing; Yan, Dandan; Gao, Qinwei; Zhan, Da; Jiang, Yuan; Liu, Xiang Yang
Abstract : A dip-coating method is designed to assemble cellulose nanocrystals into a uniaxial thin film for coaligning single-walled carbon nanotubes. Abstract : A solution-based, low-cost dip-coating method was explored to assemble cellulose nanocrystals (CNCs) into a uniaxial thin film, as confirmed by multiple microscopic tools on multiple length scales. Furthermore, this approach is readily modified for the coassembly of CNCs and a tough 1D nanoitem – single-walled carbon nanotubes into a uniaxial array.